Discover Islamic art - Museum With No Frontiers (2004)
The Permanent Collection offers four ways to sort the objects and monuments in the Discover Islamic Art Database. Results include two types of material: The material – objects and monuments – contributed by the Partners from the 14 countries who, between 2004 and 2007, set up the Discover Islamic Art Virtual Museum with the support of the European Union’s Euromed Heritage programme. Descriptions are available in Arabic, English, French and Spanish as well as in the language of the country. Objects contributed by Partners through the project Explore Islamic Art Collections, launched in 2009 with the aim of expanding the Virtual Museum’s Database. In this case, Database entries are shorter and available in English and, for some countries, also in the country’s language.